Poet Arshag Tchobanian on the border of two centuries - Avagyan, Vachagan (Bulletin of Yerevan University B: Philology, 2022)
Most of his poems Arshag Tchobanian has written during the first two decades of his literary activity - in 1890-1900. Tchobanian’s poetic experiments have been studied both in the past and in relatively new times. Presenting the already familiar material as much as possible, the article gives a special place to the valuable work “Western Armenian Poetry in 1890-1907” (1985) by famous literature specialist Vladimir Kirakosyan, where a broad analysis and evaluation of Archag Tchobanian’s poetic experiments is done. In particular, using this study, current paper’s author shows what role Tchobanian played in Western Armenian poetry on the border of two centuries. Although he did not gain serious achievements ​​marking a new stage with his experiments, but with his creative novelties he brought a completely different quality of poetry, which, being the most characteristic expression of the poetic searches of the first half of the 1890s, became a start of active movements in Western Armenian poetry in the beginning of the 20th century.
Keywords: Arshag Tchobanian; Vladimir Kirakosyan; Armenian-Armenian poetry; late 19th century; art; searches; innovation; realism; combination; aesthetics; form; tradition